Off-ice training manual for U-18 ice hockey - Lievonen, M. (2020)
Strength and conditioning is a vast field and the importance of a well-designed off-ice training program for ice hockey is extremely important. The goal of the off-ice training is to develop, not only better ice hockey players, but better athletes overall. The role of strength and conditioning in ice hockey seems to have increased in importance in the past years. Therefore, this manual got started. This product is an off-ice training manual, that includes an annual plan for the whole season, a program for strength training, speed and plyometric training, and endurance training. Also a monitoring system and testing battery are included to complement the product. This product tackles the key areas of the off-ice training and key features of the age-specific needs for u-18 athletes. Sport analysis covers the key physical elements that are needed in the game. Strength development stands as a major building block for young athletes. Speed, agility, endurance training and mobility are other training modes addressed in the product. The effects of strength training seem to have an undeniable benefit for speed and agility performance. Scientific research and textbook materials regarding to developing these abilities are addressed. Training variables for each physical ability are covered and explained. The thesis reviews different periodization models and programming structures for various times of the season. Periodization is one of the major keys to creating a structured training plan and provides a window for the best adaptations of each training modality. Monitoring is an essential part of the periodization. It will allow individual changes to the program and can indicate overtraining. Testing can dictate the effectiveness of the training program. Physical testing should be done to determine individual weaknesses and strengths. The annual plan of the off-ice training is the final product of the thesis. The training program includes an example of an annual plan and microcycle structure for the off-season, pre-season, competitive season, and transition phase. Actual training sessions of all training modes, strength, speed, agility, and conditioning are included and explained in the product. The program presents recommended testing battery and monitoring methods that can be used to evaluate the effectiveness of the training program and progress of the athletes performance. The final product is intended for ice hockey coaches. Designing a well-rounded off-ice training program takes a lot of time. All the different training modes have their own intrigue variables, and with all the other responsibilities that head-coaches have, ready to use manual might be a much-needed help As in with any scientific review, no conclusion can be made as final. The field of strength and conditioning progresses every year and more information of developing skills is presented. Therefore, the information provided in this manual is a product of this time. Even though many training methods are proven efficient over years of experimenting and studying, it does not mean that new, more efficient training methods cannot be discovered.